Assessing the Effects of Land Use Practices and Environmental Conservation in Rubanda District: A Case Study of Hamurwa Sub-County. - Mutesigensi, Samuel (Kabale University, 2023)
This study was focused on assessing the effects of land use practices and environmental conservation in Rubanda district. The study was guided by three objectives; to identify effects of land use practices on environmental conservation in Hamurwa sub-county Rubanda district, to establish policies/laws that govern land and environment in Hamurwa sub-county Rubanda district and to identify the activities that degrade the environment in Hamurwa sub-county Rubanda district. Data collection tools included questionnaires and interview guide which were used to collect data from 100 respondents mainly staff of Hamurwa sub-county, leaders and community members. Data analysis was done using Microsoft excel and the findings were presented in tables, charts and graphs. The study findings indicates that there were policies/laws that govern land and environment as they include; national land use policy with 14%, national environment Act with 20%, the land Act of 1998 with 10%, the Uganda national land policy 2013 with 16% and local policies or rules that govern land and environment with 40%. Majority of the respondents with 40% agreed that local policies or rules that govern land and environment were the major policy used by respondents from Hamurwa Sub-county Rubanda district. Findings of the study indicates that there were effects of land use practices on environment as they include; Good quality yields indicated by 18%, Increased Quantity yield or yield per acre presented by 20%, improved soil fertility presented by 36% and other factors with 26%. However majority of the respondents revealed that improved soil fertility with 36% was the most common effect affecting land use practices in Hamurwa sub-county Rubanda district. The study findings indicates that there were activities that degrades the environment which include; overpopulation with 16%, housing/settlement with 8%, land tenure with 4%, overgrazing with 12%, bush burning with 10%, over cultivation with 22%, mono cropping with 20% and other factors with 8%. However majority of the respondents revealed that over cultivation with 22% was the major activity that degrade the environment.